Isolation and characterization of the nephritogenic antigen producing anti-tubular basement membrane disease (The Rockefeller University Press, 1985)
Using monoclonal antibody affinity chromatography, we isolated a 48,000 mol wt, glucose-rich glycoprotein (3M-1) from collagenase-solubilized rabbit renal tubular basement membrane (SRTA). The purified 3M-1 protein is noncollagenous, and is capable of inducing anti-TBM (tubular basement membrane) antibodies and interstitial nephritis in susceptible hosts. Further, when SRTA, at a normally nephritogenic dose, was selectively depleted of 3M-1, it lost its ability to induce disease. As shown by immunofluorescent techniques, 3M-1 appears to be localized on rodent TBM to the exclusion of the glomerular basement membrane, but was lacking in the TBM of the LEW rat, a strain devoid of the relevant antigen of anti-TBM disease. Immunoelectron microscopy revealed that 3M- 1 was associated with the most lateral aspect of the TBM, which borders, and lies in the interstitium. These results indicate that 3M-1 is the nephritogenic antigen producing experimental anti-TBM disease.